VERIFICATION OF KEY MANAGEMENT CRYPTOGRAPHIC PROTOCOLS WITH COLORED PETRI NETS - Nadezhda S. Mogilevskaya; Sergey S. Kolchanov (Advanced Engineering Research, 2011)
The possibility of using colored Petri nets for the analysis of key distribution cryptographic protocols as an example of symmetric Needham—Schroeder protocol is reviewed and evaluated.